Novel drill structure for damage reduction in drilling CFRP composites. (November 2016) - Jia, Zhenyuan; Fu, Rao; Niu, Bin; Qian, Baowei; Bai, Yu; Wang, Fuji
Abstract: Drilling holes on CFRP components is inevitable for assembling process in the aviation industry. The drilling-induced damages frequently occur and affect not only the load carrying capacity of components but also the reliability. Therefore, it is of great urgency to enhance drilling quality on CFRP components. The article aims to propose a novel drill structure to change the cutting conditions at the drill exit and effectively reduce damages in drilling CFRP. Considering the drilling-exit constraint condition, a unique two-dimensional cutting model is established to represent the axial cutting of the main cutting edge at the drill exit. Based on the model, the effects of point of action and cutting direction on material removal at the exit are investigated, and the result indicates that cutting CFRP in the upward direction has positive effects on deflection limitation and damage reduction. In order to perform the upward cutting, a novel intermittent-sawtooth drill structure is proposed on the one-shot drill. The theoretical and geometrical analyses of the drilling process reveal that the cutting lips of the structure could reverse the cutting direction from downward to upward and thereby, reduce the drill-exit damages. Furthermore, drilling experiments are conducted and the drill structure is proved to be effective to reduce drilling damages as expected. Highlights: A cutting model considering drill-exit constraints is developed for drilling CFRP. Cutting upward is found based on the model to be positive on the damage reduction. An intermittent-sawtooth drill structure is proposed to perform the upward cutting. Burrs and delaminations are effectively suppressed by the novel drill structure.